Validation in a Brazilian population of gene markers of periodontitis previously investigated by GWAS and bioinformatic studies - Cirelli, Thamiris [UNESP]; Nepomuceno, Rafael [UNESP]; Orrico, Silvana R. P. [UNESP]; Rossa, Carlos [UNESP]; Cirelli, Joni A. [UNESP]; North, Kari E.; Graff, Mariaelisa; Barros, Silvana P.; Scarel-Caminaga, Raquel M. [UNESP] (Wiley, 2021)
Background: Bioinformatic tools and genome-wide association studies (GWAS) have led to comprehensive identification of single nucleotide polymorphisms (SNPs) associated with periodontitis in diverse populations. Here we aimed to detect and validate the association of seven SNPs as genetic markers of susceptibility to periodontitis in a Brazilian population. Methods: This case-control study assessed complete periodontal parameters of 714 subjects with periodontal status classified as healthy/mild periodontitis (n = 356) and moderate/severe periodontitis (n = 358). Genotyping for rs187238, rs352140, rs1360573, rs2521634, rs3811046, rs3826782, and rs7762544 SNPs were evaluated. Genetic-phenotype associations, and sex or smoking effects of SNPs on periodontitis were tested using multiple logistic regressions adjusted for covariates. Results: The rs2521634-AA (close to NPY gene) presented increased risk for severe periodontitis (OR = 2.34; 95% CI = 1.19–4.59). The rs3811046-GG (IL37 gene) demonstrated increased risk for moderate periodontitis (OR = 2.58; 95% CI = 1.28–5.18). Higher risk for moderate periodontitis was found in male with rs7762544-AG close to NCR2 gene. The rs352140-TT in the TLR9 gene proved to be associated with lower risk to severe periodontitis in men. The rs2521634-AA was associated with higher percentage of interproximal probing pocket depth (P =.004). Conclusions: This is the first evidence of validation in a Brazilian population of genetic markers of periodontitis previously investigated by GWAS and bioinformatics studies. SNPs in the NPY, IL37, and NCR2 genes were associated with susceptibility to moderate or severe periodontitis; whereas the TLR9 marker was associated with lower chance to develop severe periodontitis. Those SNPs had sex- and smoking-habit-specific effects on periodontitis; reinforcing the genetic profile predisposing to periodontitis.
Keywords: genetic risk; interleukin; neuropeptide Y; periodontal disease; single nucleotide polymorphism